Prostate-specific Antigen as a Predictor for the Diagnosis of Prostate Adenocarcinoma - Wilfredo Valiente Morejón; Bárbara Junco Sena; Yoel Padrón Vega; Yisel de la Caridad Ramos Águila; Idelma Castillo García (Revista Finlay)
Background: prostatic neoplasms remain asymptomatic for several years and are the second leading cause of morbidity and mortality among men over 50 years. Objective: to identify the presence of prostate adenocarcinoma through prostate-specific antigen screening in men older than 50 years. Method: a descriptive study was carried out in Consolación del Sur from January 2011 through September 2013. The universe consisted of all men (3155) aged 50 and older who underwent the test in this municipality. A survey was conducted to obtain information related to age, skin color, prostate-specific antigen results, indication for the test and year it was performed. Statistical data processing was executed using absolute frequencies, percentages and averages. Results: the screening covered 21.8 % of the population and yet 17 new cases were diagnosed. Patients aged 80 years and over predominated. The test that identifies patients at risk for prostate adenocarcinoma showed a low percentage of positivity (0.5 %). Urology specialists established more diagnosis than all family physicians in the municipality. Conclusions: the prostate-specific antigen is a useful test for the diagnosis of prostate adenocarcinoma. For that reason, it should be used as routine examination in all men older than 50 years in patients suspected of having this condition.